Diseño del sistema de gestión integrado en calidad, seguridad y salud en el trabajo bajo la norma NTC-ISO 9001:2008, OHSAS18001:2007 y el Decreto 1072 de 2015 Capitulo 6, para la empresa de construcción de estructuras en concreto; Civilia S.A. (2016)
This work aims to provide the company CIVILIA SA, the design of the Integrated Management System for Quality, Safety and Health in the workplace under the norm NTC-ISO 9001: 2008, OHSAS18001: 2007 and Decree 1072 of 2015, chapter 6, with the In order to give a systemic approach to its activities and ensure legal compliance that applies. Top management is reluctant to implement a comprehensive management system QHS because it considers it a meaningless investment with minimal results against the investment made and is based on the fact that the company has obtained numerous contracts for more than 40 years, managed to stay in the market without having a comprehensive management system, concluding that it is not necessary to implement it. You want to leave the design proposal on the management table after letting them know the reasons why it should be implemented. The implementation of the designed system will allow you to better organize your production process, generating profitability in the organization, thanks to the fact that within the objectives of the integral management system is to increase customer satisfaction and the protection and promotion of workers' health .